2017
DOI: 10.1097/ncc.0000000000000353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Slow-Stroke Back Massage on Symptom Cluster in Adult Patients With Acute Leukemia

Abstract: Oncology nurses can increase their knowledge regarding this symptom cluster and work to diminish the cluster components by using SSBM in adult leukemia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 39 publications
0
42
0
4
Order By: Relevance
“…Next, it was translated and its validity and reliability were evaluated. The reliability of this tool was assessed using the calculation of the Cronbach's alpha coefficient that was 0.86 (Miladinia, Baraz, Shariati, & Malehi, ).…”
Section: Methodsmentioning
confidence: 99%
“…Next, it was translated and its validity and reliability were evaluated. The reliability of this tool was assessed using the calculation of the Cronbach's alpha coefficient that was 0.86 (Miladinia, Baraz, Shariati, & Malehi, ).…”
Section: Methodsmentioning
confidence: 99%
“…Music therapy is one of the cognitive-behavioral methods with mental, physical, and psychological sedative effects (15,16). Massage therapy is a scientific manipulation of body textures with physiological, neurological, psychological, and biomechanical effects (17).…”
Section: Introductionmentioning
confidence: 99%
“…Two massage therapy intervention studies showed feasibility, significantly reduced progressive sleep disorder, pain, fatigue and improved sleep quality over time (Miladinia, Baraz, Shariati, & Malehi, ); and improved levels of stress and health‐related QOL (Taylor et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…An aromatherapy intervention focused on insomnia and other common symptoms among patients with acute leukaemia and reported significant improvements in tiredness, drowsiness, lack of appetite, depression, anxiety and well-being (Blackburn et al, 2017). Two massage therapy intervention studies showed feasibility, significantly reduced progressive sleep disorder, pain, fatigue and improved sleep quality over time (Miladinia, Baraz, Shariati, & Malehi, 2017); and improved levels of stress and health-related QOL (Taylor et al, 2014).…”
Section: Complementary and Alternative Therapymentioning
confidence: 99%